2007
DOI: 10.1038/nbt1374
|View full text |Cite
|
Sign up to set email alerts
|

Generation of induced pluripotent stem cells without Myc from mouse and human fibroblasts

Abstract: Direct reprogramming of somatic cells provides an opportunity to generate patient- or disease-specific pluripotent stem cells. Such induced pluripotent stem (iPS) cells were generated from mouse fibroblasts by retroviral transduction of four transcription factors: Oct3/4, Sox2, Klf4 and c-Myc. Mouse iPS cells are indistinguishable from embryonic stem (ES) cells in many respects and produce germline-competent chimeras. Reactivation of the c-Myc retrovirus, however, increases tumorigenicity in the chimeras and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

59
1,892
5
28

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 2,551 publications
(2,011 citation statements)
references
References 18 publications
59
1,892
5
28
Order By: Relevance
“…Despite significant attention from many researchers, the exact mechanisms by which Yamanaka factors lead to iPSC induction have remained difficult to dissect [20,43,44]. Among the four factors, c-Myc is not necessary for the reprogramming of somatic cells into iPSCs [45,46]. Furthermore, recent studies have shown that both mouse and human neural stem cells can be reprogrammed to iPSCs with Oct4 and Klf4, or Oct4 alone [47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Despite significant attention from many researchers, the exact mechanisms by which Yamanaka factors lead to iPSC induction have remained difficult to dissect [20,43,44]. Among the four factors, c-Myc is not necessary for the reprogramming of somatic cells into iPSCs [45,46]. Furthermore, recent studies have shown that both mouse and human neural stem cells can be reprogrammed to iPSCs with Oct4 and Klf4, or Oct4 alone [47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…38)-40) The iPS cells were also established using three factors without c-MYC, which harbors the highest risk of oncogenesis among these OSKM factors. 41) Some iPS cells even passed the most stringent test for pluripotency; tetraploid complementation. 42)- 46) The cells of tetraploid embryos can contribute to extraembryonic tissues, but not to embryonic tissues.…”
Section: Induction Of Pluripotency By Defined Factorsmentioning
confidence: 99%
“…Oct4 is considered to be a unique reprogramming factor, as it could not be replaced by other paralogous members of the POU (Pit‐Unc‐POU) protein family, while both Sox2 and Klf4 are replaceable and c‐Myc can be omitted altogether 2. Exogenous Oct4 is the most common component of reprogramming mixtures, and activation of endogenous Oct4 is a crucial step in inducing pluripotency.…”
Section: Introductionmentioning
confidence: 99%